A bandwidth reduction method for selective contents broadcasting. (14th July 2009) - Yoshihisa, Tomoki; Nishio, Shojiro
Due to the recent popularisation of digital broadcasting systems, selective contents, i.e., users watch their selected contents, have attracted great attention. For example, in a quiz program, a user selects his or her answer and watches the video content corresponding to the answer. Although a server can deliver content according to users' preferences, the necessary bandwidth to play the content continuously becomes large. However, by scheduling those streams considering the sequence in which to play them, the necessary bandwidth can be reduced. In this paper, we propose a bandwidth reduction method for selective contents broadcasting.